Potensi Ekonomi Home Industry Rumah Potong Ayam di Jalan Abubakar Lambogo Kota Makassar - Nurcahya Andriani Sari; Abdul Rahman (Jurnal Ekonomi dan Riset Pembangunan, 2023)
The home industry for chicken slaughterhouses in Makassar City is a fairly large chicken slaughterhouse, this is evidenced by the relatively high growth of chicken slaughterhouses. The purpose of writing this article is to find out the economic potential of a chicken slaughterhouse for people's income on Abubakar Lambogo street, Makassar City and to find out the response of the Makassar regional government to the existence of the home industry. This paper uses the literature review method as a basis for building theory and analysis by linking various relevant concepts. The results of the study show that the existence of this home industry business has provided many benefits to the community, both in economic and social aspects such as creating jobs and providing free health services. Makassar City Government in addressing this matter is in a very big dilemma. The reason is because these activities have a positive impact on the one hand, especially aspects of handling the economic resilience of the residents and on the other hand it has an ecological impact, both social and environmental cleanliness.